Multiplexed bead-based assay for the simultaneous quantification of human serum IgG antibodies to tetanus, diphtheria, pertussis toxin, filamentous hemagglutinin, and pertactin - Rathod, Vishal; Kadam, Laxmikant; Gautam, Manish; Gumma, Prabhu Dasu; Marke, Kevin; Asokanathan, Cathy; Douglas-Bardsley, Alex; Hassell, Laura; Bhandare, Sachin; Gupta, Sumit; Parekh, Sameer; Pujari, Pramod; et al. (Frontiers in Immunology, 2023)
Background: Luminex bead-based assays offer multiplexing to test antibodies against multiple antigens simultaneously; however, this requires validation using internationally certified reference standards. Therefore, there is an urgent need to characterize existing reference standards for multiplex immunoassays (MIA) standardization. Here, we report the development and validation of an MIA for simultaneous estimation of human serum immunoglobulin G (IgG) antibodies for pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin (PRN), diphtheria toxoid (DT), and tetanus toxoid (TT). Methods: The MIA was assessed using a panel of human serum samples and WHO reference standards; the reference standards were studied for suitability in the MIA. Purified antigens (PT, FHA, PRN, DT, and TT) were coupled to the spectrally unique magnetic carboxylated microspheres. The method was validated per the United States Food and Drug Administration (US FDA), European Medicines Agency (EMA), and International Committee of Harmonization Multidisciplinary (ICH M10) guidelines, and parameters such as precision, accuracy, dilutional linearity, assay range, robustness, and stability were assessed. Method agreements with commercially available IgG ELISA assays were also evaluated. Additionally, the study assessed the level of correlation between the IgG levels estimated by the MIA and cell-based neutralizing antibody assays for PT and DT. Results: We identified that an equimix of WHO international standards (06/142, 10/262, and TE-3) afforded the best dynamic range for all the antigens in the MIA. For all five antigens, we observed that the back-fitted recoveries using 4 parameters logistic (4PL) regression fits ranged between 80%-120% for all calibration levels, and the coefficient of variation (CV) was <20%. In addition, the difference in Mean Fluorescence Intensity (MFI) between the monoplex and multiplex format was <10% for each antigen, indicating no crosstalk among the beads. The MIA also showed good agreement with conventional and commercially available assays, and a positive correlation (>0.75) with toxin neutralization assays for PT and DT was observed. Conclusion: The MIA calibrated with WHO reference standards demonstrated increased sensitivity, reproducibility, and high throughput capabilities, which would allow the designing of robust studies for evaluating natural and vaccine-induced immunity.